2021
DOI: 10.1038/s41598-021-89155-x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous dynamics in the curing process of epoxy resins

Abstract: Epoxy resin is indispensable for modern industry because of its excellent mechanical properties, chemical resistance, and excellent moldability. To date, various methods have been used to investigate the physical properties of the cured product and the kinetics of the curing process, but its microscopic dynamics have been insufficiently studied. In this study, the microscopic dynamics in the curing process of a catalytic epoxy resin were investigated under different temperature conditions utilizing X-ray photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…Because this is an imaging technique, promising future applications may include the determination of the relative degree of polymerization in different regions of the same sample of inhomogeneous polymer networks and films. [67][68][69][70][71][72][73] The FLRAP/FRAP autofluorescence approach developed here may be amenable to monitoring additional chemical systems with viscosity changes, including diverse synthetic polymerization systems that were previously overlooked for lack of obvious fluorescence handles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because this is an imaging technique, promising future applications may include the determination of the relative degree of polymerization in different regions of the same sample of inhomogeneous polymer networks and films. [67][68][69][70][71][72][73] The FLRAP/FRAP autofluorescence approach developed here may be amenable to monitoring additional chemical systems with viscosity changes, including diverse synthetic polymerization systems that were previously overlooked for lack of obvious fluorescence handles.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in array detectors for time‐resolved microscopy [60–65] and/or use of microdrop technology [8, 66] provide possible future paths for increasing the number of simultaneous samples for high‐throughput screening approaches. Because this is an imaging technique, promising future applications may include the determination of the relative degree of polymerization in different regions of the same sample of inhomogeneous polymer networks and films [67–73] . The FLRAP/FRAP autofluorescence approach developed here may be amenable to monitoring additional chemical systems with viscosity changes, including diverse synthetic polymerization systems that were previously overlooked for lack of obvious fluorescence handles.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] From the perspective of dynamic analysis, X-ray photon correlation spectroscopy (XPCS) studies have been also conducted. [16][17][18] In addition to bulk systems, epoxy resins have been widely used in thin film structures, such as coatings, insulator films, and adhesives. Thus, the physical properties of epoxy-resin thin films, such as electrical insulation, 19 mechanical properties in composite materials, 20,21 and chemical state at substrate interface, [22][23][24][25] have attracted considerable interest and have been vigorously investigated.…”
Section: Introductionmentioning
confidence: 99%
“…13–15 From the perspective of dynamic analysis, X-ray photon correlation spectroscopy (XPCS) studies have been also conducted. 16–18…”
Section: Introductionmentioning
confidence: 99%
“…X-ray photon correlation spectroscopy (XPCS) is a powerful technique for probing the dynamics of opaque concentrated colloidal systems and heterogeneous dynamics on a wide range of spatial scales by analyzing the temporal uctuations of the scattered speckles obtained by partially coherent X-ray scattering. [20][21][22][23][24][25][26][27] We previously studied the behavior of nematic colloidal liquid crystals formed by biomineral-based rod-like hybrids by XPCS. 28 We observed that they exhibited faster dynamics in the direction of the director than in the perpendicular direction in the LC phase when kept for a long period.…”
Section: Introductionmentioning
confidence: 99%